Adjustment of egg laying by both hosts and intraspecific brood parasites in a beetle. (5th July 2021) - Richardson, Jon; Dobson, Sarah; Ford, Lucy E.; Smiseth, Per T.
Abstract: Brood parasites lay their eggs in the nests of other females, thereby shifting the costs of offspring care onto others. Given that care is costly, potential hosts should evolve mechanisms to avoid brood parasitism. Meanwhile, brood parasites should evolve mechanisms to circumvent host defences. Here we investigate whether hosts or intraspecific brood parasites adjust their egg laying behaviour as a mechanism to reduce or increase the effectiveness of brood parasitism. We use the burying beetle Nicrophorus vespilloides as our study system, in which hosts and brood parasites lay their eggs in the soil around a carcass controlled by the host. To test whether females adjust their egg laying behaviour when breeding as a host or brood parasite, we used an experimental design with three treatments: hosts, where focal females bred alongside a smaller female; brood parasites, where focal females bred alongside a larger female; and controls, where focal females bred alone. We used focal females from a narrowly defined size range to control for potential effects of body size. We found that hosts delayed the start of egg laying, which may allow them to recognise brood parasitic offspring that arrive too early. Meanwhile, brood parasites laid their eggs over an extended period, which may increase the chances that their egg laying overlapped with the host. Our results suggest that adjusting egg laying behaviour is a mechanism used by both hosts and brood parasites that may contribute to the differences in reproductive success shown in prior studies.